VG161 activates systemic antitumor immunity in pancreatic cancer models as a novel oncolytic herpesvirus expressing multiple immunomodulatory transgenes. Issue 1 (14th September 2022) - Shen, Yinan; Song, Wei; Lin, Danni; Zhang, Xiaozhen; Wang, Meng; Li, Yuwei; Yang, Zifan; Guo, Sida; Wang, Zijun; Sheng, Jianpeng; Murad, Yanal; Ding, Jun; et al.
Abstract: The VG161 represents the first recombinant oncolytic herpes simplex virus type 1 carrying multiple synergistic antitumor immuno‐modulating factors. Here, we report its antitumor mechanisms and thus provide firm theoretical foundation for the upcoming clinical application in pancreatic cancer. Generally, the VG161‐mediated antitumor outcomes were analyzed by a collaboration of techniques, namely the single‐cell sequencing, airflow‐assisted desorption electrospray ionization‐mass spectrometry imaging (AFADSI‐MSI) and nanostring techniques. In vitro, the efficacy of VG161 together with immune checkpoint inhibitors (ICIs) has been successfully shown to grant a long‐term antitumor effect by altering tumor immunity and remodeling tumor microenvironment (TME) metabolisms. Cellular functional pathways and cell subtypes detected from patient samples before and after the treatment had undergone distinctive changes including upregulated CD8+ T and natural killer cells. More importantly, significant antitumor signals have emerged since the administration of VG161 injection. In conclusion, VG161 can systematically activate acquired and innate immunity in pancreatic models, as well as improve the tumor immune microenvironment, indicative of strong antitumor potential. The more robusting antitumor outcome for VG161 monotherapy or in combination with other therapies on pancreatic cancer is worth of being explored in further clinical trials.